Human embryonic stem cell lines derived from single blastomeres of two 4-cell stage embryos - Geens, Mieke (Oxford University Press, 2009)
BACKGROUND: Recently, we demonstrated that single blastomeres of a 4-cell stage human embryo are able to develop into blastocysts with inner cell mass and trophectoderm. To further investigate potency at the 4-cell stage, we aimed to derive pluripotent human embryonic stem cells (hESC) from single blastomeres. METHODS: Four 4-cell stage embryos were split on Day 2 of preimplantation development and the 16 blastomeres were individually cultured in sequential medium. On Day 3 or 4, the blastomere-derived embryos were plated on inactivated mouse embryonic fibroblasts (MEFs). RESULTS: Ten out of sixteen blastomere-derived morulae attached to the MEFs, and two produced an outgrowth. They were mechanically passaged onto fresh MEFs as described for blastocyst ICM-derived hESC, and shown to express the typical stemness markers by immunocytochemistry and/or RT–PCR. In vivo pluripotency was confirmed by the presence of all three germ layers in the teratoma obtained after injection in immunodeficient mice. The first hESC line displays a mosaic normal/abnormal 46, XX, dup(7)(q33qter), del(18)(q23qter) karyotype. The second hESC line displays a normal 46, XY karyotype. CONCLUSION: We report the successful derivation and characterization of two hESC lines from single blastomeres of four split 4-cell stage human embryos. These two hESC lines were derived from distinct embryos, proving that at least one of the 4-cell stage blastomeres is pluripotent.